Evolution of Intestinal Gases and Fecal Short-Chain Fatty Acids Produced in vitro by Preterm Infant Gut Microbiota During the First 4 Weeks of Life - Wang, Xuefang; Li, Juan; Li, Na; Guan, Kunyu; Yin, Di; Zhang, Huating; Ding, Guodong; Hu, Yong (Frontiers in Pediatrics, 2021)
Background: The production of intestinal gases and fecal short-chain fatty acids (SCFAs) by infant gut microbiota may have a significant impact on their health, but information about the composition and volume of intestinal gases and SCFAs in preterm infants is scarce. Objective: This study examined the change of the composition and volume of intestinal gases and SCFA profiles produced by preterm infant gut microbiota in vitro during the first 4 weeks of life. Methods: Fecal samples were obtained at five time points (within 3 days, 1 week, 2 weeks, 3 weeks, and 4 weeks) from 19 preterm infants hospitalized in the neonatal intensive care unit (NICU) of Shanghai Children's Hospital, Shanghai Jiao Tong University between May and July 2020. These samples were initially inoculated into four different media containing lactose (LAT), fructooligosaccharide (FOS), 2'fucosyllactose (FL-2), and galactooligosaccharide (GOS) and thereafter fermented for 24 hours under conditions mimicking those of the large intestine at 37.8°C under anaerobic conditions. The volume of total intestinal gases and the concentrations of individual carbon dioxide (CO2), hydrogen (H2), methane (CH4), and hydrogen sulfide (H2S) were measured by a gas analyzer. The concentrations of total SCFAs, individual acetic acid, propanoic acid, butyric acid, isobutyric acid, pentanoic acid, and valeric acid were measured by gas chromatography (GC). Results: The total volume of intestinal gases (ranging from 0.01 ml to 1.64 ml in medium with LAT; 0 ml to 1.42 ml with GOS; 0 ml to 0.91 ml with FOS; and 0 ml to 0.44 ml with FL-2) and the concentrations of CO2, H2, H2S, and all six fecal SCFAs increased with age (p-trends < 0.05). Among them, CO2 was usually the predominant intestinal gas, and acetic acid was the predominant SCFA. When stratified by birth weight (< 1500 g and ≥ 1500 g), gender, and delivery mode, the concentration of CO2 was more pronounced among infants whose weight was ≥ 1500 g than those <1500 g (p-trends < 0.05). Conclusions: Our findings suggested that the intestinal gases and SCFAs produced by preterm infant gut microbiota in vitro increased with age during the first 4 weeks of life.